2005
DOI: 10.1093/pubmed/fdi060
|View full text |Cite
|
Sign up to set email alerts
|

Can knowledge protect against acute mountain sickness?

Abstract: Trekkers who indicated that they would act safely in the event of developing moderate to severe AMS were significantly less likely to be suffering from AMS when interviewed and had ascended significantly less altitude in the preceding 72 h being more likely to adhere to recommended ascent guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 6 publications
0
20
3
Order By: Relevance
“…Numerous previous studies showed reduced effects of sex (Hackett et al, 1976;Maggiorini et al, 1990;Schneider et al, 2002;Vardy et al, 2006;Wang et al, 2010) and age (Schneider et al, 2002;Vardy et al, 2005;Wang et al, 2010) on AMS, but some studies found a higher risk of AMS in women (Honigman et al, 1993) or men ( Johnson and Rock, 1988), and in younger adults (Hackett et al, 1976;Honigman et al, 1993) or the elderly (Maggiorini et al, 1990). Our results suggest that sex and age differences are of little importance in terms of the prevalence and severity of AMS among climbers of Mt.…”
Section: Effect Of Demographic Issues (Sex and Age)contrasting
confidence: 45%
See 1 more Smart Citation
“…Numerous previous studies showed reduced effects of sex (Hackett et al, 1976;Maggiorini et al, 1990;Schneider et al, 2002;Vardy et al, 2006;Wang et al, 2010) and age (Schneider et al, 2002;Vardy et al, 2005;Wang et al, 2010) on AMS, but some studies found a higher risk of AMS in women (Honigman et al, 1993) or men ( Johnson and Rock, 1988), and in younger adults (Hackett et al, 1976;Honigman et al, 1993) or the elderly (Maggiorini et al, 1990). Our results suggest that sex and age differences are of little importance in terms of the prevalence and severity of AMS among climbers of Mt.…”
Section: Effect Of Demographic Issues (Sex and Age)contrasting
confidence: 45%
“…Fuji. Moreover, our sample size (n = 2267) was much larger than those typically found in previous epidemiological studies (n = 130-827 participants) (Hackett et al, 1976;Maggiorini et al, 1990;Basnyat et al, 2000;Schneider et al, 2002;Vardy et al, 2005Vardy et al, , 2006Mairer et al, 2009Mairer et al, , 2010, although one previous study had over 3000 participants (Honigman et al, 1993).…”
Section: Sample Sizementioning
confidence: 79%
“…Preparedness plays a key role in reducing certain risks when trekking at high altitude. A previous study has shown that foreign national trekkers in the Nepal Himalaya who were better prepared, in terms of their understanding of AMS, were more likely to adhere to recommended ascent guidelines and experience fewer altitude-related illnesses (Vardy et al, 2005). However, within our study (which did not assess participants' understanding of AMS), approximately 90% of trekking groups included foreign nationals who had received or read information on altitude illness and acclimatization.…”
Section: Preparation Of Groups With and Without Medical Problemsmentioning
confidence: 74%
“…For example, athletes may train at high altitudes, which can result in erythrocytosis. Some studies suggest that a high–low method of sleeping at high altitude followed by training at low altitude is a better training strategy than training or sleeping at either high or low altitudes alone 54. Some athletes have tried sleeping at simulated high altitude by using low oxygen tents.…”
Section: Nondrug Performance-enhancing Measuresmentioning
confidence: 99%